The Problem of Integrating Pancasila Student Profile with Islamic Religious Education Material Through the Implementation of Content Differentiation Learning in Elementary School - Ihwanah, Al; Ismail, Fajri; Astrid, Annisa; Maryamah; Sukirman (JIP Jurnal Ilmiah PGMI, 2024)
This study aims to describe the problem of integrating Pancasila student profile with Islamic Religious Education materials through the implementation of content differentiation learning in elementary school. This research employs a qualitative approach with a case study design. The subjects include teachers, principals, and students from several elementary schools in the research area, while the object of study is the implementation of content differentiation in PAI learning. Data were collected through in-depth interviews, observations, and document analysis. Data analysis was conducted interactively through data reduction, data presentation, and conclusion drawing. Data validity was ensured using source and method triangulation. This study found that integrating the Pancasila Student Profile with Islamic Religious Education (PAI) materials through content differentiation is hindered by limited teacher understanding, lack of planning time, and insufficient resources. The causes include low teacher competence, an unsupportive curriculum, and weak collaboration. Recommended solutions include teacher training, curriculum development, and strengthening stakeholder collaboration.The conclusion highlights the importance of improving teacher competence through continuous professional development, creating practical guidelines for content differentiation, and fostering collaboration among stakeholders to provide adequate resources. The study recommends intensive training for teachers and the development of a curriculum that supports the implementation of content differentiation, aiming to shape students' character in alignment with the values of the Profile of Pancasila Student.